Calsium Supplementation with Rasbora sp. to Prevent Loss of Bone Mineral Density during Gonadotropin-releasing hormone Agonis Long-term Treatment - Enrico Hervianto; Hardyan Sauqi; Farida Heriyani; Juhairina (Indonesian Journal of Obstetrics and Gynecology, 2022)
Background. Gonadotropin-releasing hormone (GnRH) agonist widely used to induce hypoestrogenic climate overcoming any benign gynecologic abnormalities such as endometriosis, adenomyosis, or various cause of abnormal uterine bleeding. Hypoestrogenic cause some of adverse effect mainly loss of bone mineral density (BMD). Suplementation of calcium improve loss in BMD, hence prevent development of osteoporosis. Certain area of Indonesia shows specific biodiversity, for example South Borneo has its wetland biodiversity in swamp and river. Processed food from fishery like Rasbora sp. (locally called Seluang fish) is local favourite due to access and economical reason. Method. Studies included 24 reproductive age (15-49 years old) female on agonist GnRH leuprolide acetate 11,25 mcg regimen given subcutaneously. Measurement of bone mineral density was done twice within 3 months apart, before and after first agonist GnRH treatment. During observation, subject was divided to one of three daily supplementation belows, placebo containing saccharum lactis, grinded powder of 500 mg of calcium, or grinded powder of dried Rasbora sp containing 500 mg of calcium. Measurement pre- and post- supplementation was count using bone quality index with Osteosys of Sonost 3000. Result. Placebo supplementation group in GnRH agonist has bone mineral density loss of -22,7201 greater than 500 mg grinded powder of lactate calcium dan grinded powder of rasbora sp, respectively -4,4570 and -3,3634 after 3 months of trial. Homogeneity test shown p=0.031 level of significancy and ANOVA resulted a significant difference from three classes. Post Hoc resulted calcium lactate supplementation 18,26 + 3,20 greater (p = 0.001) and grinded powder of Seluang 19,36 + 3,20 greater (p = 0.000). Both form of calcium lactate and fish powder supplementation have no significant differences. Conclusion. Calcium supplementation in both of calcium lactate powder and natural resources help maintaining bone mineral density during GnRH agonist treatment. Seluang fish (Rasbora sp.), abundantly found along Indonesia people especially in South Borneo, has similar potency with pharmaceutical calcium lactate product in same weight. Fishery product, has beneficial trace element for bodies, 84 mg of calcium (Ca), 6,81 % of magnesium (Mg), 13,4 mg of iron (Fe), dan 3.97 % of zinc (Zn). Keyword: Bone mineral density, Calcium supplementation, Agonist GnRH, Rasbora Sp.